2018
DOI: 10.1371/journal.ppat.1007285
|View full text |Cite
|
Sign up to set email alerts
|

The MAPK kinase BcMkk1 suppresses oxalic acid biosynthesis via impeding phosphorylation of BcRim15 by BcSch9 in Botrytis cinerea

Abstract: The mitogen-activated protein kinase (MAPK) cassette of the cell wall integrity (CWI) pathway is primarily responsible for orchestrating changes of cell wall. However, functions of this cassette in other cellular processes are not well understood. Here, we found that the Botrytis cinerea mutant of MAPK kinase (BcMkk1) displays more serious defects in mycelial growth, conidiation, responses to cell wall and oxidative stresses, but possesses less reduced virulence than the mutants of its upstream (BcBck1) and do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 96 publications
1
38
0
Order By: Relevance
“…Among the SM pathways detected, one can mention those of the toxins botrydial and botcinic acid, both involved in B. cinerea virulence [55,56], but also oxalic acid. Although not essential to B. cinerea virulence, this organic acid contributes to lesion expansion through acidification essential for lytic enzymes [66,70,71]. The strong reduction (100x) of oxaloacetate hydrolase (OAH) in the ∆sak1 mutant may contribute to its reduced aggressiveness.…”
Section: Differentially Abundant Proteins Are Enriched In Functional mentioning
confidence: 99%
“…Among the SM pathways detected, one can mention those of the toxins botrydial and botcinic acid, both involved in B. cinerea virulence [55,56], but also oxalic acid. Although not essential to B. cinerea virulence, this organic acid contributes to lesion expansion through acidification essential for lytic enzymes [66,70,71]. The strong reduction (100x) of oxaloacetate hydrolase (OAH) in the ∆sak1 mutant may contribute to its reduced aggressiveness.…”
Section: Differentially Abundant Proteins Are Enriched In Functional mentioning
confidence: 99%
“…Besides growth defects associated with the bac point mutation, we explored the relationship of the S1407 site in BAC to cell wall integrity, a parameter that is closely related to fungal development and virulence [15]. The sensitivity of point mutants to cell wall-damaging agents and degrading enzymes was determined ( Figure 6).…”
Section: The S1407p Mutation In Bac Alters the Fungal Cell Wall Integmentioning
confidence: 99%
“…The MAPK signaling pathway transmits signals through the sequential activation of three interacting protein kinases. In B. cinerea, it has been reported that three MAPKs, Bmp1, Bmp3, and Bcsak1, are involved in growth and pathogenicity [13][14][15][16]. Furthermore, the filamentous fungi have evolved light signaling pathways which regulate growth, development and metabolism and allow them to adapt to changes in the environment.…”
mentioning
confidence: 99%
“…Among the SM pathways detected, one can mention those of the toxins botrydial and botcinic acid, both involved in B. cinerea virulence (Dalmais et al, 2011;Rossi et al, 2011), but also oxalic acid. Although not essential to B. cinerea virulence, this organic acid contributes to lesion expansion through acidification essential for lytic enzymes (Kunz et al, 2006;Müller et al, 2018;Yin et al, 2018). The strong reduction (100x) of oxaloacetate hydrolase (OAH) in the ∆sak1 mutant may certainly contribute to its reduced aggressiveness.…”
Section: Differentially Abundant Proteins Are Enriched In Functional mentioning
confidence: 99%
“…The finding that OAH production is under Sak1 control is interesting as well. A recent publication revealed that OAH expression and the production of oxalate is controlled by the MAPKK of the CWI pathway via the protein kinase Sch9 without involvement of the MAPK Bmp3 (Yin et al, 2018). It would now be interesting to analyse the respective roles of Sch9 and Sak1 in addition to their connection with respect to the regulation of OAH production.…”
Section: Link To Other Signaling Pathwaysmentioning
confidence: 99%